New Hypothesis Insight of Structural Properties on Four Tau Peptide Fragments in Alzheimer's Disease: Origin from the Histidine Behaviors - Sun, Yue; Li, Changgui; Wang, Jinping; Shi, Hu (Chemistry : a European journal, 2023)
During protein folding and misfolding, structural properties and aggregation tendency can be significantly influenced by histidine behaviors (tautomeric behaviors and protonation behaviors). The original reasons were derived from the net charge changes and the various N/N−H orientation on imidazole rings. In the current study, total 18 independent REMD simulations were performed to investigate the histidine behaviors on four Tau peptide fragments (MBD, including R1, R2, R3, and R4 fragments). We found that, compared to R1, R2, R3 except (ϵδ), and R4 systems with flexible structural features, only R3(ϵδ) has dominating conformational structure (possibility of 81.3 %) with three β‐strand structures in parallel β‐sheet structures at I4‐K6 and I24‐H26, as well as antiparallel β‐sheet structure at G19‐L21. Importantly, the H25 and H26 residues (in R3(ϵδ) system) are directly involved in the sheet structure formations and strong H‐bonded interactions (possibility range of 31.3 %–44.7 %). Furthermore, the donors and acceptors analysis confirmed that only R3(ϵδ) shows faraway amino acids interaction features in both H25 and H26 residues, and such cooperation effects of two histidine residues contribute to current structural features. The current study will be helpful to further enrichment of the histidine behavior hypothesis, it provides new insight for understanding protein folding and misfolding. The structural properties and aggregation tendency of four Tau peptide fragments are subject to significant modulation by histidine behaviors, including its tautomeric and protonation states. Notably, the R1, R2, and R4 fragments exhibit a preference for unstable and flexible structural features, whereas only R3(ϵδ) displays a propensity for stable three β‐strand structures.